2002
DOI: 10.1289/ehp.021101069
|View full text |Cite
|
Sign up to set email alerts
|

Daily average exposures to respirable particulate matter from combustion of biomass fuels in rural households of southern India.

Abstract: Indoor air pollution resulting from combustion of biomass fuels in rural households of developing countries is now recognized as a major contributor to the global burden of disease. Accurate estimation of health risks has been hampered by a paucity of quantitative exposure information. In this study we quantified exposures to respirable particulate matter from biomass-fuel combustion in 436 rural homes selected through stratified random sampling from four districts of Tamil Nadu, India. The study households ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
162
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(178 citation statements)
references
References 27 publications
16
162
0
Order By: Relevance
“…Past experience (Balakrishnan et al, 2002) in Tamil Nadu, an adjoining state in Southern India had shown that within households using solid fuels, exposures to indoor air pollution from solid fuel use vary according to kitchen type. The type of kitchen has not been shown to influence exposures in households using clean fuels.…”
Section: Selection Of Study Householdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past experience (Balakrishnan et al, 2002) in Tamil Nadu, an adjoining state in Southern India had shown that within households using solid fuels, exposures to indoor air pollution from solid fuel use vary according to kitchen type. The type of kitchen has not been shown to influence exposures in households using clean fuels.…”
Section: Selection Of Study Householdsmentioning
confidence: 99%
“…Some 12-24 h determinations of respirable particulate concentrations have also been carried out, reporting 24-h means in the range of 300-3000 mg/m 3 (Saksena et al, 1992;McCracken and Smith, 1998). More recently, systematic, large-scale 24-h measurements of respirable particulates have been reported (Ezzati et al, 2000;Albalak et al, 2001;Parikh et al, 2001;Balakrishnan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Data on personal exposure to pollutants in biomass smoke are necessary for analysis of association with disease outcomes, but has been measured or estimated in few studies (Ezzati et al, 2000;Naeher et al, 2001;Balakrishnan et al, 2002;Bruce et al, 2004;Dasgupta et al, 2006;Mestl et al, 2007;Dionisio et al, 2008;McCracken et al, 2009). In particular, a metric of usual exposure is desired because exposure may vary from day to day and health effects may depend on cumulative exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our study has revealed considerable variation in the release of SO2. Factors responsible for the difference in concentrations and variation of indoor air pollutants could be explained in relation to the type of material or substance burnt, burning intensity, room or enclosed area, ventilation rate, spatial distribution of pollutants, duration of the monitoring regimen etc, for which these factors may vary in emission release (Balakrishnan et al, 2002;Smith et al, 2004). For instance, Salvi et al (2006) reported lower levels of CO (6.5 ppm) relative to this study when door and window were closed.…”
Section: Discussionmentioning
confidence: 99%